Jacques Gilard: dos ponencias feministas - Helena Araújo (Caravelle)
In honour of the admired professor, Helena Aráujo evokes two occasions on which she listened to two of his lectures in the University of Pau during two congresses (1996 & 2004) about «the place, the representations, the status and the part played by women in Latin-American society and culture». Analysing the first tales written by Marvel Moreno, born in Barranquilla, Jacques Gilard would emphasize the «humiliation inflicted to the feminine body as a characteristic of patriarchal system». His second lecture, about Marvel Moreno’s mother’s diaries, would show their great importance «for the understanding of the genesis and the contents of her daughter’s literary works».